Knowledge Quality Effect on Process Based Management Effectiveness - Mustapha, Ishamuddin; Md Nor, Khalil; Ikbar Abd Wahab, Mohd; Anwar Abu Bakar, Fairul; Amran Mohd Daril, Mohd; Awang, Mazlan; Nordin, Latipah (International Journal of Engineering and Technology, 2018)
The objective of this study is to examine the effect of knowledge quality (KQ) on process-based management effectiveness (PBME). The knowledge quality for effective process-based management is an increasingly important issue to the business community. The current review conducted on research work in Knowledge Management and Quality Management Systems field has shown that there are deficiencies in the current research domain which, investigation on knowledge quality and its effect on process-based management was not an interest of previous researchers. The deficiencies shed light for future research that explores in details the effect of KQ on PBME. This issue has initiated interest amongst academicians to empirically examine the effect of knowledge quality on the process-based management effectiveness especially on the ISO9001:2008 certified organization. This study has found that KQ has significant direct effect with PBME in the certified ISO9001:2008 organization. This is indicated by the path coefficients and t-statistics of the relationship between KQ and PBME using PLS-SEM. The results is in line with the opinion derived from semi-structured interview conducted and also accords with earlier research which showed that the quality of knowledge can improve the performance of the processes. The evidence from this result suggests that organization should emphasize on the quality of knowledge to increase the process-based management effectiveness.Â